2005
DOI: 10.1039/b510756c
|View full text |Cite
|
Sign up to set email alerts
|

Chirality transfer in the aza-[2,3]-Wittig sigmatropic rearrangement

Abstract: The aza-[2,3]-Wittig sigmatropic rearrangements of substrates derived from enantiomerically pure alanine, valine and serine with phenyl and ester anion stabilising groups were investigated for their efficiency in chirality transfer. It was found that a methyl substituent at the stereogenic centre of the rearrangement precursors was inadequate to control the alkene stereoselectivity and enantioselectivity of the rearrangement. Ester stabilised anions of valine and serine derivatives were the most successful wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Preliminary solution-phase experiments were undertaken to explore the feasible reaction conditions and to establish the required modifications for a practical SPOS. As shown in Scheme , N -Boc- O -TBDPS- dl -serine 2 , was prepared from dl -serine in an 84% yield. Subsequent esterification of the protected serine 2 with benzyl alcohol under DIC-medicated coupling conditions gave the benzyl ester 3 in good yield (92%).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary solution-phase experiments were undertaken to explore the feasible reaction conditions and to establish the required modifications for a practical SPOS. As shown in Scheme , N -Boc- O -TBDPS- dl -serine 2 , was prepared from dl -serine in an 84% yield. Subsequent esterification of the protected serine 2 with benzyl alcohol under DIC-medicated coupling conditions gave the benzyl ester 3 in good yield (92%).…”
Section: Resultsmentioning
confidence: 99%
“…For the more elaborately functionalized amino acids previously mentioned ( 11e – j , Scheme ), an alternative process was employed because of the somewhat low reactivity of the Weinreb amides in subsequent C-acylation reactions, relative to N -acyl imidazoles (Scheme ). N-Protected-amino acids 11e – j were allowed to react with carbonyl diimidazole at 0 °C, to directly provide the corresponding acyl imidazoles 16a – f in 65–91% yield (Scheme )…”
Section: Resultsmentioning
confidence: 99%
“…15 The stereoselectivity of the forming product can also be induced by chiral catalysts or auxiliaries, or through chirality transfer. [16][17][18][19][20] Somfai and coworkers have developed a stoichiometric asymmetric rearrangement reaction using Lewis acids to generate products with excellent enantioselectivities and diastereoselectivities. Our preliminary experiments with cinnamyl-substituted methyl ester derivative 1a showed that the use of methyl ester as an electron-withdrawing group (EWG) gave poor results.…”
Section: Scheme 1 [23]-rearrangement Of N-allylic Ammonium Ylidesmentioning
confidence: 99%